Macromolecular crystallization and crystal perfection - Chayen, Naomi E.; Helliwell, John R.; Snell, Edward H. (Oxford : Oxford University Press, 2010)
Structural biology is key to our understanding of the mechanisms of biological processes. This text describes current methods and future frontiers in crystal growth and use of X-ray and neutron crystallography, in the context of automation of crystallization and generation of synchrotron X-ray and neutron beams.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crystallization; Crystallography; Macromolecules